2018
DOI: 10.2478/acve-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Canine Babesiosis: Where Do We Stand?

Abstract: Canine babesiosis is a tick-borne disease caused by protozoal haemoparasites of different Babesia species. Babesiosis is one of the most important globally extended and quickly spreading tick-borne infections of dogs. This comprehensive review gives an in-depth overview of Babesia species currently identifi ed in dogs together with relevant vector tick species and their geographical distribution, life cycle and transmission of parasite. The main mechanisms in the pathogenesis of babesiosis are described and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 181 publications
(251 reference statements)
1
26
0
1
Order By: Relevance
“…Ми погоджуємся з думкою [17], що зміни в селезінці виникають внаслідок хронізації бабезіозу. При цьому збудники хвороби депонуються у паренхіматозних структурах селезінки (й інших лімфоїдних органах) і стають недосяжними для лікарських засобів [7,10]. Будь-який патогенний стимул, як то: запальні процеси, стрес-реакції тощо, може призвести до реакцій організму, пов'язаних з мобілізацією функцій цих органів.…”
Section: результати досліджень та їх обговоренняunclassified
“…Ми погоджуємся з думкою [17], що зміни в селезінці виникають внаслідок хронізації бабезіозу. При цьому збудники хвороби депонуються у паренхіматозних структурах селезінки (й інших лімфоїдних органах) і стають недосяжними для лікарських засобів [7,10]. Будь-який патогенний стимул, як то: запальні процеси, стрес-реакції тощо, може призвести до реакцій організму, пов'язаних з мобілізацією функцій цих органів.…”
Section: результати досліджень та їх обговоренняunclassified
“…Canine babesiosis can be caused by Babesia canis, Babesia vogeli, Babesia Rossi, Babesia caballi, Babesia gibsoni, Babesia conradae and Babesia microti-like sp. (Bilic, Kules, Bariac, & Mrljak, 2018). In Brazil, molecular identification of both B. vogeli (Passos, Geiger, Ribeiro, Pfister, & Zahler-Rinder, 2005) and B. gibsoni (Trapp et al, 2006) has already been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These protozoa are transmitted to mammals through the blood meal of infected ticks. In general, the genus Babesia stands out in the group of piroplasms that infect dogs (Bilić et al, 2018). Initially, these species were classified according to its morphology in erythrocytes in "large" (2.5-5.0 µm long) and "small" (1.0-2.5 µm long) forms being recognized as B. canis and B. gibsoni, respectively (Laha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of molecular phylogenetic analysis, in particular that of the 18S rRNA gene, it was recognized that the subspecies are in fact distinct species, mainly B. rossi, B. canis, and B. vogeli (Irwin, 2009;Köster et al, 2015;Bilić et al, 2018). Babesia canis is endemic in Europe but has been reported sporadically around the world, B. rossi is endemic in South Africa and B. vogeli is found worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation